1984
DOI: 10.1113/jphysiol.1984.sp015284
|View full text |Cite
|
Sign up to set email alerts
|

Influence of circulating catecholamines on protein secretion into rat parotid saliva during parasympathetic stimulation.

Abstract: SUMMARY1. Secretion ofproteins by rat parotid glands in response to parasympathetic nerve stimulation was studied in vivo during pentobarbitone anaesthesia.2. Parasympathetic stimulation (3-10 Hz) via the auriculotemporal nerve resulted in a copious flow of saliva low in protein. In contrast, sympathetic stimulation (5 Hz) via the cervical sympathetic trunk evoked saliva low in volume but high in protein.Nevertheless, the specific concentrations of amylase and peroxidase (mg/mg protein) and the ratio of amylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 29 publications
2
25
0
3
Order By: Relevance
“…One possible explanation for our findings is suggested by the recent observation that, even under anaesthesia, a degree of catecholamine circulating in the blood can influence the secretion of amylase on parasympathetic nerve stimulation of rat parotid glands, especially from glands made supersensitive by chronic sympathectomy (Anderson et al 1984). Furthermore, circulating catecholamines have been found to influence parotid acinar secretion in conscious rabbits (Gj6rstrup, 1980).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One possible explanation for our findings is suggested by the recent observation that, even under anaesthesia, a degree of catecholamine circulating in the blood can influence the secretion of amylase on parasympathetic nerve stimulation of rat parotid glands, especially from glands made supersensitive by chronic sympathectomy (Anderson et al 1984). Furthermore, circulating catecholamines have been found to influence parotid acinar secretion in conscious rabbits (Gj6rstrup, 1980).…”
Section: Discussionmentioning
confidence: 78%
“…This is unlikely to be a consequence of metabolic and adaptational alterations leading to a changed role for parasympathetic nerves, since parasympathetic nerve stimulation per se of chronically sympathectomized glands (Anderson et al 1984) was not associated with similar evidence of degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary concentrations of PRP have been found to be altered by systemic administration of isoprenaline and propranolol, as mentioned earlier; we have now shown that they are also influenced directly by sympathetic nerves since removal of the nerves leads to a decrease in PRP secretion upon parasympathetic stimulation. The increase in amylase as a proportion of secreted protein was not seen following chronic sympathectomy (Anderson et al 1984), thus this change may be restricted to an early phase following sympathectomy, but a time-based study will be required to confirm this.…”
Section: Methodsmentioning
confidence: 98%
“…Protein concentrations of saliva were determined both by the Lowry assay (Lowry, Rosebrough, Farr & Randall, 1951) and absorbance at 215 nm (abs2l5nm) using a human albumin/globulin standard (Sigma). Amylase activity was assayed by the method of Bemfeld (1955) and converted to weight equivalents of amylase (Loyter & Schramm, 1962 (Schneyer & Hall, 1966; Anderson, Garrett, Johnson, Kauffman, Keller & Thulin, 1984;Asking & Emmelin, 1985). The increased amylase:protein and Lowry protein:abs2l5nm (L:A) ratios of saliva from sympathectomized glands indicate that the proportions of different proteins in parasympathetically evoked saliva are altered by sympathectomy.…”
Section: Methodsmentioning
confidence: 99%
“…The rats were provided with a femoral venous catheter and fitted with a tracheal cannula and a rectal thermometer; body temperature was maintained at 38 "C by a thermostatically controlled blanket. In order to exclude cholinergic and adrenergic influences or the action of circulating catecholamines (Anderson et al 1984;Malhotra & Wakade, 1987), if any, on the secretory response, atropine sulphate (Sigma), the a-adrenoceptor blocker phentolamine mesylate (Ciba Geigy) and the P-adrenoceptor blocker propranolol hydrochloride (Sigma) were injected through the femoral venous catheter (2 mg kg-I of each) as a precaution. The blockers were given 10 min before the start of the infusion.…”
Section: Methodsmentioning
confidence: 99%